PENGARUH METODE PEMBAYARAN CASH ON DELIVERY (COD) TERHADAP KURIR DI ERA DIGITAL - Umul Sidikoh; Abdurohim; Arna Soraya Hutasuhut; Kasih Bunga Melati; Besar Agung Martono (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
The purpose of this study is to determine the effect of the Cash On Delivery payment system on couriers during the buying and selling transaction process. The method used in this research is using the desk study method, which is carried out by studying the literature on COD cases, online payment system users and other data based on related documents, such as mass media, electronic media, and activity reports. The results of this research are to provide suggestions for business people, such as marketplaces, sellers and expeditions to make better schemes and provide education to customers about these schemes